1997
DOI: 10.1051/aas:1997370
|View full text |Cite
|
Sign up to set email alerts
|

A stellar coronograph for the COME-ON-PLUS adaptive optics system

Abstract: Abstract. The detection of faint emissions very close to much brighter objects is required in several different fields of astrophysics, for example in the search for planetary disks. We present here a coronograph that we built to work with come-on-plus, the ESO adaptive optics system, high angular resolution being of key importance in allowing observations close to a central, occulted object. The first results are presented and analyzed in order to establish the performance of this instrument in terms of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 6 publications
(3 reference statements)
0
30
0
1
Order By: Relevance
“…Though it corresponds to an additional perturbation, a deterministic contribution can easily be calibrated. Nonetheless, observing acquisitions have shown that the major noise-source limitation in high-contrast imaging is another class of instrumental speckles, the quasi-static speckles (Beuzit et al 1997;Oppenheimer et al 2001;Marois et al 2003;Boccaletti et al 2003Boccaletti et al , 2004Hinkley et al 2007). Quasi-static speckles correspond to slowly varying instrumental wavefront aberrations (amplitude and phase errors) present in the system, which finally dominate the companion signal.…”
Section: Introductionmentioning
confidence: 99%
“…Though it corresponds to an additional perturbation, a deterministic contribution can easily be calibrated. Nonetheless, observing acquisitions have shown that the major noise-source limitation in high-contrast imaging is another class of instrumental speckles, the quasi-static speckles (Beuzit et al 1997;Oppenheimer et al 2001;Marois et al 2003;Boccaletti et al 2003Boccaletti et al , 2004Hinkley et al 2007). Quasi-static speckles correspond to slowly varying instrumental wavefront aberrations (amplitude and phase errors) present in the system, which finally dominate the companion signal.…”
Section: Introductionmentioning
confidence: 99%
“…Details on the coronograph and its performance are given in Beuzit et al (1997). We iteratively centered the star "behind" the mask.…”
Section: Program Goal and Observing Equipmentmentioning
confidence: 99%
“…The interest in stellar coronagraphy is relatively recent (Bonneau et al 1975;Smith & Terrile 1984;Malbet 1996;Beuzit et al 1997;Mouillet et al 1997), and nowadays mainly stimulated by the exoplanets searches. The direct imaging of an exoplanet is the most exciting objective for high contrast imaging techniques: it will provide valuable information such as its mass (removing the ambiguity due to the radial velocities technique), its albedo and its atmosphere chemical composition if spectral information can be obtained.…”
Section: Introductionmentioning
confidence: 99%